Hydrate Attenuation Characteristics Based on the Patchy-Saturation Model - Liu, Pengqi; Huang, Handong; Hu, Liguo; Mao, Shuang; Tian, Zhongbin; Shen, Youyi (Frontiers in Earth Science, 2022)
At present, attenuation characteristics of hydrate applicable to the seismic frequency band are still controversial. In this study, the dispersion and attenuation characteristics of hydrate in different occurrence modes were defined from the mesoscale perspective, and the saturation of hydrate in the study area is estimated. Based on effective medium theory and cementation theory, the skeleton elastic modulus of the sedimentary layer was obtained in the present study. The variation of P-wave attenuation with hydrate saturation was obtained by patchy-saturation theory. P-wave attenuation increased with saturation when hydrate occurred in suspension mode. P-wave attenuation decreased with saturation when hydrate occurred in particle-contact or cementation mode. The particle-contact mode and cementation mode hydrate made the P-wave attenuation peak shift to the right. The influence of the cementation mode on attenuation was greater than that of the particle-contact mode. The conclusions of this study are applicable to the frequency range of seismic exploration thus solving the problems of hydrate saturation prediction and resource quantity calculation assessment in the study area.